THE USE OF PICTURE SERIES TO TEACH WRITING PROCEDURE TEXT - Margana, M. Wisnu; Sada, Clarry; RiyantI, Dwi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract The paper discusses the effectiveness of using picture series to increase students’ ability in writing procedure text at the eleventh grade students of SMK-SMTI Pontianak. The aim of this research was to know whether teaching writing procedure text by using picture series was effective to the eleventh grade students.The research method was pre- experimental research with one group pretest-posttest design. The population was the eleventh grade students. The sample was XI D which consist 15 students. The technique of data collection was measurement technique and the tool of data collection was a written test. The result of T-test was 8.4 and the effect size was 2.2. It means that the effect size was high effect with ES > 0.8 (2.2 > 0,8). Based on the result, the null hypothesis was rejected and the alternative hypothesis was accepted. The conclusion that the use of picture series is effective to teach students’ writing procedure text. Keywords : Writing, Procedure text, Picture series